Development of Soft Skills Oriented to SPA Services (Solus Per Aqua) in the Vocational Education Teaching Factory - Nurvitasari, Fitria; Supraptono, Eko; Kusumastuti, Adhi; Sutopo, Yeri (Universitas Negeri Semarang, 2023)
This research aimed to develop a SPA services-oriented learning model to increase students soft skills. The present study applied Research and Development (RnD) with the ADDIE model. A validity and reliability instrument in the module was conducted by 4 media experts, 5 material experts, 10 teachers, and 30 students. the researcher applied feasibility, practicality, and effectivity analyses after the validity and reliability test. The content validity test result (Content Validity Ratio) showed that the CVI of media and material experts were 0.98 and 0.97, or it can be stated as a valid category. The reliability test depicted that Cronbach's Alpha got 0.707 and 0.766 categorized as reliable. In terms of feasibility, the research achieved 81.25% from media experts and 88.88% from material experts with a very feasible category. The practicality test results from teacher and student responses obtained 79.30% and 76.50% of the percentage or declared as in the practical category. In addition, the effectiveness test showed that the soft skills aspect was 56.06%, and the psychomotor aspect achieved 70.56% or stated as the quite effective category. According to the analysis results, the developed learning module has been declared feasible, practical, and effective to be used in learning body treatment material and can improve the soft skill and psychomotor aspects of Beauty and SPA Vocational School students.